Celebrity advocacy and public engagement: The divergent uses of celebrity. (July 2015) - Markham, Tim
This article sounds a cautionary note about the instrumental use of celebrity advocacy to (re)engage audiences in public life. It begins by setting out the steps necessary to achieve public recognition of a social problem requiring a response. It then presents empirical evidence which suggests that those most interested in celebrity, while also paying attention to the main stories of the day, are least likely to participate in any form of politics. However, this does not rule out the possibility of forging a link between celebrity and public engagement, raising questions about what would potentially sustain such an articulation. After discussing the broader cultural context of celebrity advocacy, in which perceived authenticity functions as a valorised form of symbolic capital, the article outlines a phenomenological approach to understanding the uses audiences make of celebrity advocacy, using the example of a Ewan McGregor UNICEF appeal for illustration. It concludes that while media encounters with celebrities can underpin a viewer's sense of self, this is as likely to lead to the rationalisation of inaction as a positive response to a charity appeal.